Theoretical simulation and experimental verification of the competition between different recombination channels in GaN semiconductors. Issue 36 (31st August 2022) - Zhang, Hai-Shan; Shi, Lin; Liu, Zheng-Hui; Xu, Geng-Zhao; Song, Wen-Tao; Wang, Ya-Kun; Xu, Zhong-Jie; Yang, Xiao-Bao; Zhao, Yu-Jun; Yang, Xue-Lin; Shen, Bo; Wang, Lin-Wang; et al.
Abstract : We simulate the time-resolved decay process of the yellow band in GaN based on the first principles, and the simulated decay lifetimes are confirmed in our experiments. Abstract : The dynamic competition of deep defect levels related to recombination processes is a crucial factor for a wide range of applications in semiconductors; however, time-resolved luminescence spectroscopy is very complex and challenging for clear explanations, and in time-resolved photoluminescence (TRPL) experiments, it is difficult for a single instrument to observe the decay processes across several orders of magnitude simultaneously. Based on the Shockley–Read–Hall (SRH) model, we present a method to simulate defect-related TRPL processes on timescales ranging from the picosecond to millisecond scale. Our approach considers the competition among the band edge and defect-related radiative and nonradiative recombination channels. In an n-type GaN sample, we demonstrate that following pulse laser excitation, the substitutional defect CN related yellow luminescence (YL) exhibits a double-exponential decay. The fast decay in hundreds of picoseconds is due to the band edge emission (BE), while the well-known slow decay at the microsecond scale is induced by electron relaxation from the conduction band to the defect state. The fast and slow decay lifetimes of YL in verification experiments are all in good agreement with our simulated results. This work provides an explicit physical picture of defect-related luminescence and the competition of different recombination channels in GaN.